1992
DOI: 10.1177/002221949202500703
|View full text |Cite
|
Sign up to set email alerts
|

The Success of College Students with Learning Disabilities: Factors Related to Educational Attainment

Abstract: This study reports on the educational attainment of 62 college students with learning disabilities as compared to a sample of 58 peers matched on gender and ACT composite score (+/- 1 point or exact match). All students were native English speakers and were enrolled as degree candidates in a small, competitive, private, midwestern college. Groups were compared on age, high school preparation and performance, college grades, GPA at the end of each year of study, graduation and academic failure rate, and time ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
1
7

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 11 publications
2
68
1
7
Order By: Relevance
“…A study of a single university found that students with Attention Deficit Disorder (ADD) are more likely to be put on academic probation (earning a GPA below a 2.0) than students without ADD (Frazier et al, 2007). Another study found that students with learning disabilities have more D and P (passing a pass/fail class) grades than students without learning disabilities (Vogel & Adelman, 1992). Students with health impairments may face attitudinal barriers from college advisors, professors, family or friends because of perceived inability to tackle challenging coursework, which could diminish their sense of self-efficacy and restrict their access to college-level coursework, especially in math and science ( et al, 2005).…”
Section: Author Manuscriptmentioning
confidence: 99%
“…A study of a single university found that students with Attention Deficit Disorder (ADD) are more likely to be put on academic probation (earning a GPA below a 2.0) than students without ADD (Frazier et al, 2007). Another study found that students with learning disabilities have more D and P (passing a pass/fail class) grades than students without learning disabilities (Vogel & Adelman, 1992). Students with health impairments may face attitudinal barriers from college advisors, professors, family or friends because of perceived inability to tackle challenging coursework, which could diminish their sense of self-efficacy and restrict their access to college-level coursework, especially in math and science ( et al, 2005).…”
Section: Author Manuscriptmentioning
confidence: 99%
“…Bien qu'aucune recherche proprement dite ait traité, jusqu'à ce jour, des Aksamit, 1987;Anderson, 2012;Bonnelli et al, 2010;Bourke, Strehorn, et Silver, 2000;Fichten et al, 1988;Field, 2003;Fonosch et Schwab, 1981;Houck et al, 1992;Ihori, 2012;Keefe, 2008;Leyser et al, 2003;McWaine, 2012;Pearman, Barnhart, Huang, et Melblom, 1992;Satcher, 1992;Scott et Gregg, 2000;Stoler, 1992;Vogel et Adelman, 1992;Vogel et al, 1999;Wilczenski et Gillespie-Silver, 1992;Wolforth et Roberts, 2010), les recherches québécoises n'y font pas exception. Selon Keefe (2008) Adaptation, dans une certaine mesure, de leur enseignement Soutien pédagogique additionnel à ces élèves pour les aider à comprendre la matière enseignée Peu de problèmes recensés quant à la gestion des comportements des étudiants ayant des troubles de santé mentale en classe 32 Aksamit, 1987;Anderson, 2012;Bigaj et al, 1999;Bonnelli et al, 2010;Chalifoux, 2004;Cook, 2007;CREPUQ, 2010;Fichten et al, 1988;Fichten, Asuncion, et al, 2003;Fichten et al, 2006;Fichten, Jorgensen, et al, 2003;FNEEQ, 2010;Ihori, 2012;Leyser, 1988;Leyser et al, 2003;McWaine, 2012;Murray et al, 2000;…”
Section: Apports Des Recherches Québécoises Sur Les Représentations Sunclassified
“…Selon Keefe (2008) Adaptation, dans une certaine mesure, de leur enseignement Soutien pédagogique additionnel à ces élèves pour les aider à comprendre la matière enseignée Peu de problèmes recensés quant à la gestion des comportements des étudiants ayant des troubles de santé mentale en classe 32 Aksamit, 1987;Anderson, 2012;Bigaj et al, 1999;Bonnelli et al, 2010;Chalifoux, 2004;Cook, 2007;CREPUQ, 2010;Fichten et al, 1988;Fichten, Asuncion, et al, 2003;Fichten et al, 2006;Fichten, Jorgensen, et al, 2003;FNEEQ, 2010;Ihori, 2012;Leyser, 1988;Leyser et al, 2003;McWaine, 2012;Murray et al, 2000;Nguyen et Fichten, 2007;Potvin et Rousseau, 1993;Quinlan et al, 2012;Satcher, 1992;St-Onge et al, 2009 b;Tremblay et Fournier, 2008;Vogel et Adelman, 1992;Wolforth, Mai 2010a;Wolforth et Roberts, 2010 Tableau 3 Anderson, 2012;Bonnelli et al, 2010;Brochu et Moffet, 2010;CREPUQ, 2010;Ihori, 2012;McWaine, 2012;Quinlan et al, 2012;StOnge et al, 2009 En conclusion, bien que de nombreux concepts (Anadon, 2006). Au fil des décennies, plus d'une vingtaine de définitions ont été développées pour décrire ce qu'est la recherche qualitative/interprétative (Potter, 1996) Finalement, c'est au regard de tous ces présupposés épistémologiques que la méthodologie privilégiée demeure celle inhérente à une recherche qualitative/interprét...…”
Section: Apports Des Recherches Québécoises Sur Les Représentations Sunclassified
See 1 more Smart Citation
“…Among students studied by Vogel and Adelman (1992), some dyslexic students cited positive experiences. They remembered teachers who helped them along the way, had confidence in their abilities, gave them encouragement in the face of disappointments, and had a significant irapact on their development and success.…”
Section: The Decision To Enter the Field Of Educationmentioning
confidence: 99%